Ecological Roles of Coleoptera Associated with Carcasses in Caatinga - Santos, Wellington Emanuel dos; Alves, Ana Claudia Firmino; Farias, Rodrigo Cesar Azevedo Pereira; Creão-Duarte, Antonio José (EntomoBrasilis, 2013)
The ecological roles of Coleoptera fauna associated with pig carcasses exposed in a Caatinga area were examined. Tray, pitfall and modified Shannon traps were settled together to collect these insects during two seasons (dry and rainy). 4,851 beetles were collected, belonging to 19 families and 88 species. The most abundant ecological category was predator/parasite (72.7%), followed by omnivorous (15.1%), necrophagous (10.9%) and incidental (1.3%). Future researches on the biology of predator/parasite species are required to understand their possible forensic utility for postmortem interval estimate. Papel Ecológico de Coleoptera Associados a Carcaças em Área de Caatinga Resumo. O papel ecológico da coleopterofauna associada a carcaças de porcos em uma área de Caatinga foi examinado. Para captura desses insetos foram utilizadas armadilhas do tipo bandeja, pitfall e Shannon modificada, durante duas estações (seca e chuvosa). 4.851 coleópteros foram coletados, pertencentes a 19 famílias e 88 espécies. A categoria ecológica mais abundante foi predador/parasita (72,7%), seguida por onívoro (15,1%), necrófago (10,9%) e incidental (1,3%). Futuros estudos sobre biologia das espécies predadoras/parasitas são necessários para se determinar sua possível utilidade forense na estimativa do intervalo pós-morte.